What Drives Bangladeshi Consumers' Use of Online Food Delivery Applications? Investigating the Role of Trust in Repeat Purchase Intention - Yesmin, Shayala (2024)
The rapid expansion of digital technology-based applications has altered the various aspects of our lives, with smartphones now perceived as multifunctional devices that serve purposes beyond mere communication. In 2024, more than 4.88 billion people are using smartphones globally, showing a sharp upward trend. Several scholarly findings suggest that consumers' motivations vary significantly when using various smartphone applications. However, despite these differences, the impact of trust on the continued use intention of these apps is not fully explored, especially in the field of online food delivery applications (OFDAs). Likewise, an emerging country like Bangladesh, with an over 174 million population and 77 million active internet users, along with growing smartphone penetration, presents promising opportunities for OFDAs, yet there is a significantly limited research focus in this area. Realizing the research gap and the importance of trust, this thesis intends to explore the factors more profoundly that affect consumer trust building in the online food delivery apps market and the influence of trust on the continuance use intention of Bangladeshi consumers. An extended Technology Accepted Model (TAM) is proposed as its theoretical foundation, and a quantitative research technique is adopted to measure the impact of trust on the continuance purchase intention of OFDAs. A combined total of 134 valid responses were collected via an online survey, and these collected data were analyzed using statistical techniques, employing both IBM SPSS 26.0 and PLS-SEM 4.0. The research findings revealed trust is a pivotal determinant of consumers' intentions to use OFDAs repeatedly. The findings further suggest that the two key factors of the TAM model, perceived usefulness and ease of use, are greatly influenced by operational efficiency and the user-friendliness of the app respectively. Furthermore, both factors exhibit a strong correlation with trust. However, menu visualization, personalization, and order management were not identified as significant predictors for Bangladeshi consumers. This thesis contributes to the academic understanding by bridging the gap of the foundational TAM model by including additional external variables and providing area-specific insights for a developing economy. The practical and managerial implications offered by this thesis will assist the OFDA service providers in formulating consumer trust-building and experience optimization strategies.